2022
DOI: 10.1002/aenm.202200654
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Incorporation of V and Mn Element into Polyanionic NASICON for High Energy‐Density and Long‐Lifespan Zn‐Ion Storage

Abstract: batteries have attracted great attention. [2,3] Among them, aqueous Zn-ion batteries (AZIBs) shows apparent merits of abundant zinc sources, low development cost, high security, and environmental friendliness. More importantly, the chemical stability of metal zinc in a water-oxygen environment is much superior than other alkali metals and polyvalent metals, thus in favor of the design of aqueous batteries. [4,5] However, the revolution of AZIBs is still at its early stage and far from the practical application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 61 publications
0
56
0
Order By: Relevance
“…Zn anodes are widely used in aqueous zinc-ion batteries (ZIBs) for their distinct advantages: (1) zinc metal possesses an ultrahigh theoretical volumetric and gravimetric capacity of 5855 mA h cm –3 and 820 mA h g –1 , respectively; (2) Zn has good compatibility with neutral or weakly acidic aqueous solution; and (3) commercial Zn foil is easily available and inexpensive. , However, the dendrite problem seriously hinders the development of Zn metal anodes in aqueous ZIBs. Young’s modulus of Zn is much higher than that of Li, indicating that zinc dendrites are more likely to penetrate the separator and cause a short circuit of the battery . Furthermore, the shaggy dendrite is loosely connected to the Zn substrate, and the charges on the electrode surface tend to accumulate at the dendritic root, which may cause the dendrite detachment and the formation of “dead Zn,” further leading to the decrease in Coulombic efficiency (CE). , Therefore, a lot of research work has been put into inhibiting the formation and growth of zinc dendrite, such as zinc surface coating, current collector optimizing, alloying, and so on. Although these modification strategies improve the cycling performance of the Zn anode to a certain extent, they sacrifice some advantages of the zinc metal anode, such as good electrical conductivity, fast interfacial reaction kinetics, or high volumetric capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Zn anodes are widely used in aqueous zinc-ion batteries (ZIBs) for their distinct advantages: (1) zinc metal possesses an ultrahigh theoretical volumetric and gravimetric capacity of 5855 mA h cm –3 and 820 mA h g –1 , respectively; (2) Zn has good compatibility with neutral or weakly acidic aqueous solution; and (3) commercial Zn foil is easily available and inexpensive. , However, the dendrite problem seriously hinders the development of Zn metal anodes in aqueous ZIBs. Young’s modulus of Zn is much higher than that of Li, indicating that zinc dendrites are more likely to penetrate the separator and cause a short circuit of the battery . Furthermore, the shaggy dendrite is loosely connected to the Zn substrate, and the charges on the electrode surface tend to accumulate at the dendritic root, which may cause the dendrite detachment and the formation of “dead Zn,” further leading to the decrease in Coulombic efficiency (CE). , Therefore, a lot of research work has been put into inhibiting the formation and growth of zinc dendrite, such as zinc surface coating, current collector optimizing, alloying, and so on. Although these modification strategies improve the cycling performance of the Zn anode to a certain extent, they sacrifice some advantages of the zinc metal anode, such as good electrical conductivity, fast interfacial reaction kinetics, or high volumetric capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Na 1s spectra plotted in Figure h show three characteristic peaks located at 1070.5, 1071.4, and 1072.3 eV, representing the Na + ions with varied bonding properties originating from Na2 sites (18e), V sites (12c), and Na1 sites (6b), respectively. In contrast to the pure NVP, it displays an extra Na-related chemical interaction in the high binding energy region, confirming the valid substitution of V with Na. , In the case of V 2p high-resolution XPS spectra (Figure i), the bands located at 524.2 and 517.2 eV can be assigned to the trivalent V in the NVP-Na2.5% sample. These results illustrate that the introduced Na + ions are lodged at the V site and Na2 site, and a similar phenomenon was also reported in Mg-doped NVP materials …”
Section: Resultsmentioning
confidence: 61%
“…The corresponding CV curves and pseudocapacitance proportion of NVP and NVP-Na2.5% with varied scanning rates are shown in Figure S12. As seen, the pseudocapacitive proportions of NVP-Na2.5% are 82, 85, 87, 89, and 91% at scanning rates of 0.2, 0.4, 0.6, 0.8, and 1.0 mV s −1 , respectively, larger than that of the pure NVP sample (52,59,63,68, and 71%, respectively), as seen in Figure 4d,g. It can be observed that the pseudocapacitive contribution gradually increases as the scanning rate increases, revealing the prominent surface reactions at high current rates.…”
Section: ■ Results and Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Compared to the overwhelming H 2 O and OH − signals assigned to ZVO at fully discharged HVO d electrode (Figure 6e), GP-HVO d shows less variation of H 2 O peak during cycling, further verifying the significance of GP to retain the interfacial stability. The V 2p spectra from GP-HVO d (Figure S22a, Supporting Information) show that V 5+ cations are partially reduced to V 4+ and V 3+ in discharge, which is highly reversible when charged back to 1.6 V. [34] Correspondingly, the intensity variation of Zn 2p characteristic peaks at 1045.4 and 1022.2 eV proves the high reversibility of Zn 2+ intercalation/deintercalation (Figure S22b, Supporting Information). [35] The uniform distribution of V, O, and Zn elements over the HVO d bulk phase in discharged GP-HVO d electrode also verifies the successful Zn 2+ intercalation (Figure 6f ).…”
Section: Resultsmentioning
confidence: 93%